Geodynamic Processes Monitoring of Subway Infrastructure Using Geodetic and Remote Sensing Methods - Khamit, Nurzhan; Jangulova, Gulnar; Kakimzhanov, Yerkin; Kyrgyzbay, Kudaibergen; Zhumatayev, Serik; Atalykova, Nazym; Kozhaev, Zhenis (Salehan Institute of Higher Education, 2025)
This article examines the development of a methodology for monitoring geodynamic processes during the construction of the Almaty metro using an integrated approach that incorporates geodetic methods, laser scanning, and aerospace technologies. The study aims to enhance the safety of underground structures in the context of complex engineering-geological conditions and high-density urban environments. Monitoring was conducted at the